2016
DOI: 10.3390/met6080175
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Zn-Rich Phase and Corrosion/Oxidation Behavior of Sn–8Zn–3Bi Alloy

Abstract: Abstract:The microstructure of Sn-8Zn-3Bi alloy was refined by increasing the solidification rate and the correlation between Zn-rich phase and the corrosion/oxidation behavior of the alloy was investigated. The Zn-rich phase transforms from coarse flakes to fine needles dispersed in the β-Sn matrix with the increase of the cooling rate. The transformation of Zn-rich precipitates enhances the anticorrosive ability of Sn-8Zn-3Bi alloy in 3.5 wt.% NaCl solution. On the contrary, Sn-8Zn-3Bi alloy with a fine need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…It is well known that the oxide film is formed in the oxidation process of the alloys, but their oxidation behavior varies greatly due to the differences in elemental content and preparation process. There are several publications concerning the oxidation behavior of alloy materials [11,12]. Zhao et al [13] found that the addition of 2.5 at.% Al to Cu-20Ni-Cr alloy contributed to forming continuous external scales of chromia under lower Cr content.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the oxide film is formed in the oxidation process of the alloys, but their oxidation behavior varies greatly due to the differences in elemental content and preparation process. There are several publications concerning the oxidation behavior of alloy materials [11,12]. Zhao et al [13] found that the addition of 2.5 at.% Al to Cu-20Ni-Cr alloy contributed to forming continuous external scales of chromia under lower Cr content.…”
Section: Introductionmentioning
confidence: 99%